O olhar revolucionário em As Meninas - Franco Júnior, Arnaldo [UNESP]; Oliani, Nara Gonçalves [UNESP] (My University, 2013)
We analyzed here, Lia de Melo Shultz, one of the protagonists of As meninas, Lygia Fagundes Telles. Incarnation of the revolutionary romanticism of 60- 70 years of the century XX, she is the most representative character of a double crisis: the political authoritarianism of the military dictatorship and patriarchy. We highlight of the characteristic features of narrative character, exploring their actions and ideas and their role in the dramatic conflict. To contextualize the fable, we make use of texts Boris Fausto, Nadine Habert, Elio Gaspari and Leonardo Pinheiro.

Analisamos, aqui, Lia de Melo Shultz, uma das protagonistas de As meninas, de Lygia Fagundes Telles. Encarnação do romantismo revolucionário dos anos 60-70 do séc. XX, ela é a personagem mais representativa de uma dupla crise: a do autoritarismo político da ditadura militar e a do patriarcalismo. Destacamos da narrativa os traços característicos da personagem, explorando suas ações e ideias e sua função no conflito dramático. Para contextualizar a fábula, valemo-nos de textos de Bóris Fausto, Nadine Habert, Élio Gaspari e Leonardo Pinheiro.
Keywords: As meninas; Ditadura Militar; Lygia Fagundes Telles; Romantismo Revolucionário; As meninas; Military Dictatorship; Lygia Fagundes Telles; Revolutionary Romanticism